The efficacy of digital media tools to promote a healthy diet in children: A systematic review of intervention studies - Dallagiacoma, Giulia; Alberti, Federica; Odone, Anna (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Proper nutrition during childhood and puberty is essential to ensure healthy growth of children and good health in adulthood. Different types of interventions have been suggested to promote nutritional health in children. This systematic review aims to summarize the available evidence from experimental studies on the efficacy of digital media tools for the promotion of a healthy diet in school-aged children.Methods: According to PRISMA guidelines, a literature search was conducted in the three main electronic databases (PubMed/Medline, Embase e Scopus) until April 2022. We included all experimental studies assessing the effectiveness of digital media tools for nutritional health promotion in children from 5 to 12 years of age.Results: Four studies were included in our analysis, all carried out in school settings. Three of them investigated the use of a videogame, while one study involved watching a cartoon. Each intervention tested was effective in promoting a healthy diet in school-aged children in the short term, regardless of the type of intervention and age of the children involved. A statistically significant increase was observed post-intervention in all studies, both in knowledge of food groups and food frequencies, and in practices (i.e. the amount of fruit and vegetables servings consumed per meal), although the effect faded over time (when follow-up was available).Conclusions: Digital media tools can be used to effectively implement health promotion interventions to improve knowledge and adherence to healthy diets in school-aged children. Further studies are needed to assess the long-term effectiveness of these interventions.